Comparative evaluation of reverse transcriptase-quantitative polymerase chain reaction assays for the detection of Japanese encephalitis virus in swine oral fluids - Lyons, Amy Christina (Kansas State University, 2018)
Japanese encephalitis virus (JEV) is a mosquito-borne flavivirus maintained among swine and avian species. In infected pigs, replication of JEV leads to the onset of viremia and the development of neurological and reproductive disease in young and naïve pregnant animals. The high-titer viremia levels associated with JEV infection in pigs, whilst important to the enzootic transmission cycle responsible for viral maintenance, also have human health implications within the zoonotic cycle. Sensitive and specific veterinary diagnostic methods capable of readily detecting JEV infection are critical components of JEV surveillance programs in the Asian Pacific region. In this study, reverse transcriptase-quantitative polymerase chain reaction (RT-qPCR) assays were evaluated for use in veterinary diagnosis of JEV. Our hypotheses for this research project were that RT-qPCR assays with fewer oligonucleotide mismatches between the primers and probes of the assays and JEV genomes will be more sensitive for the diagnosis of JEV infection and that oral shedding of JEV in swine would allow for detection of viral RNA using oral fluids. The sensitivity and specificity of three RT-qPCR assays for the detection of JEV were determined using tissue culture fluids of five representative JEV strains belonging to four endemic genotypes. The first assay (assay #1), targeting the highly conserved NS5 gene and 3UTR regions, provided optimum detection for the current predominant genotype, GI-b. All three assays were highly specific for JEV when tested against other selected flaviviruses in the JEV serocomplex. A rope-based collection method allowed for the simplified collection of oral fluids from three-week-old piglets challenged with endemic JEV strain JE-91. These fluids were then evaluated using RT-qPCR assays for the presence of viral RNA. The results suggest that the shedding of JEV in oral fluids can be readily detected and that non-invasive oral fluid collection can serve as a novel sampling method for the diagnosis and surveillance of JEV in swine.
Keywords: Japanese encephalitis virus; Oral fluids; Swine; Diagnostic assay